-6z-6=-12z+12

Simple and best practice solution for -6z-6=-12z+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6z-6=-12z+12 equation:


Simplifying
-6z + -6 = -12z + 12

Reorder the terms:
-6 + -6z = -12z + 12

Reorder the terms:
-6 + -6z = 12 + -12z

Solving
-6 + -6z = 12 + -12z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '12z' to each side of the equation.
-6 + -6z + 12z = 12 + -12z + 12z

Combine like terms: -6z + 12z = 6z
-6 + 6z = 12 + -12z + 12z

Combine like terms: -12z + 12z = 0
-6 + 6z = 12 + 0
-6 + 6z = 12

Add '6' to each side of the equation.
-6 + 6 + 6z = 12 + 6

Combine like terms: -6 + 6 = 0
0 + 6z = 12 + 6
6z = 12 + 6

Combine like terms: 12 + 6 = 18
6z = 18

Divide each side by '6'.
z = 3

Simplifying
z = 3

See similar equations:

| 9x-6+6x-1+82=180 | | ((-2w^2)/(v^4))^3 | | 5(-2)-2x=20 | | 1/40*n=60 | | 8x^2+21x-28=0 | | 5y+4x=20 | | 1/40*x100=60 | | 2/10x=10 | | x+2=x^2+3x-4 | | x-8.3=-4.5 | | x+2=x^2+2x-4 | | 4x^6-4x^5-8x^4-9x^2+9x+18=0 | | p+37=15 | | 4n+7n=20 | | 2*n=327 | | 0=-1/2x+4 | | (2w-1)2=4(w-3)2 | | m^2+4m+13=-8 | | x=1/9*7/8 | | -7/8*1/9= | | 25x^-3y^4/35x^5y^2 | | m^2-n^2=24 | | xy+16xy*3= | | -16x^2+250x+300=0 | | 2x/3+5/7=x/7-1 | | 38w-79=39-38w | | 1/2x-8=5/16 | | 2(x-3)+3x=39 | | 17=-42x-11 | | -2n=-34 | | F9/5=C+32 | | 6(x+2)+2x=46 |

Equations solver categories